A microglia clonal inflammatory disorder in Alzheimer’s disease - Vicario, Rocio; Fragkogianni, Stamatina; Weber, Leslie; Lazarov, Tomi; Hu, Yang; Hayashi, Samantha Y; Craddock, Barbara; Socci, Nicholas D; Alberdi, Araitz; Baako, Ann; Ay, Oyku; Ogishi, Masato; et al. (eLife, 2025)
Somatic genetic heterogeneity resulting from post-zygotic DNA mutations is widespread in human tissues and can cause diseases, however, few studies have investigated its role in neurodegenerative processes such as Alzheimer’s disease (AD). Here, we report the selective enrichment of microglia clones carrying pathogenic variants, that are not present in neuronal, glia/stromal cells, or blood, from patients with AD in comparison to age-matched controls. Notably, microglia-specific AD-associated variants preferentially target the MAPK pathway, including recurrent CBL ring-domain mutations. These variants activate ERK and drive a microglia transcriptional program characterized by a strong neuro-inflammatory response, both in vitro and in patients. Although the natural history of AD-associated microglial clones is difficult to establish in humans, microglial expression of a MAPK pathway activating variant was previously shown to cause neurodegeneration in mice, suggesting that AD-associated neuroinflammatory microglial clones may contribute to the neurodegenerative process in patients. Around 10% of people aged over 65 are estimated to have Alzheimer’s disease. This progressive neurodegenerative condition leads to death of brain cells, memory loss, confusion and other life-altering symptoms. Somatic mutations are changes in the genetic information of a cell other than sperm or eggs, which can result in alterations in gene function. As the mutant cells multiply, they form clones that also carry these changes – potentially resulting in groups of cells that behave differently from those in which those mutations are absent. Despite their importance, the role of somatic mutations in Alzheimer’s disease remains poorly understood. To investigate this question, Vicario, Fragkogianni, Weber, Lazarov et al. examined the genetic material of brain and blood cells obtained from individuals who had died either of Alzheimer’s disease, or of other causes. The team focused their analysis on around 700 genes previously associated with neurodegenerative conditions. The results showed that, compared to individuals whose death was not due to neurological illnesses, harmful variants of those genes were present in higher numbers in the microglia cells of around 25% of Alzheimer’s patients in their series. No such increase was detected in other blood or brain cell populations, regardless of the individuals’ cause of death. Microglia are cells tasked with helping to repair damage and fight off infections in the brain. Many of the harmful gene variants found in this population switched on a cell pathway known as the MAP Kinase pathway, which activated the cells and caused them to multiply. This, in turn, led to inflammation and may contribute to the death of neurons. Together these findings indicate that developing a new class of therapeutics that inhibits the MAP Kinase pathway in microglia may help prevent irreversible brain damage in some patients with Alzheimer’s disease.